Single-phase uncontrolled full-wave rectifier on a three-phase AC generator. - Anggara Trisna Nugraha; Rama Arya Sobhita (Journal of Marine Electrical and Electronic Technology, 2023)
A rectifier circuit is designed to convert alternating current (AC) generated by a generator into direct current (DC). The primary component used in this circuit is a diode. A rectifier can be either controlled or uncontrolled, with both types operating on the principle of converting an AC voltage source into a DC voltage source. One key advantage of a single-phase rectifier system is its ability to deliver high output power, as the negative voltage of the AC signal is converted into a positive voltage. In an uncontrolled rectifier circuit, the addition of a capacitor serves as an active filter, minimizing ripple and ensuring a more stable DC output. The methodology for this study includes several stages: identification, analytical calculations, system flowchart development, simulation design, and data collection related to measurements. By following these steps, we can gain a comprehensive understanding of the full-wave single-phase rectifier circuit in a three-phase AC generator, ultimately leading to a well-founded conclusion.